Insurers’ Legal Liability in Rejecting Life Insurance Claims: An Analysis of the Medan High Court’s Decision No. 47/PDT/2025/PT MDN - Dhian Indah Astanti Dhian Indah Astanti; Wafda vivid izziyana; Eva Dwi (Universitas Muhammadiyah Surakarta, 2025)
ABSTRACT Purpose of the Study: This research aims to analyze the legal responsibility of insurers in rejecting life insurance claims based on policyholders’ non-material information. This study analyzes the Decision of the Medan High Court No. 47/PDT/2025/PT MDN and compares it with legal practices in Malaysia. Methodology: This research applied the normative juridical method with an analysis of legal regulations, legal doctrines, and court decisions. It also employed the legal comparison method between the legal systems in Indonesia and Malaysia. Results: Results of this research found that the rejection of claims by insurance companies due to non-material or administrative information is invalid according to the law. The judicial assembly emphasizes the principle of contractual justice and the protection towards the insured. Thus, they declare that only information with material characteristics can be used as a valid basis to reject claims. Applications of this Study: Results of this research can be used to strengthen the legal protection for policyholders in the life insurance practice. Apart from that, this study may be used as a reference for formulating policies and reforming the insurance industry both at the national and regional levels. Novelty/Originality of this Study: The novelty of this research lies in its comparative approach to the materiality principle in life insurance contracts. This research shows a difference between the normative approach in Indonesia and the factual evidence-based approach in Malaysia, enriching insight into legal protection in the life insurance industry as well as the urgency of renewing practical norms to make them more just and transparent. Keywords: Life Insurance, Claims, Substantial Justice, Insurers’ Responsibility. ABSTRAK Tujuan Penelitian:Penelitian ini bertujuan untuk menganalisis tanggung jawab hukum perusahaan asuransi dalam menolak klaim asuransi jiwa berdasarkan informasi non-material pemegang polis. Penelitian ini menganalisis Putusan Pengadilan Tinggi Medan No. 47/PDT/2025/PT MDN dan membandingkannya dengan praktik hukum di Malaysia. Metodologi:Penelitian ini menggunakan metode yuridis normatif dengan analisis peraturan perundang-undangan, doktrin hukum, dan putusan pengadilan. Penelitian ini juga menggunakan metode perbandingan hukum antara sistem hukum di Indonesia dan Malaysia. Hasil: Hasil penelitian ini menemukan bahwa penolakan klaim oleh perusahaan asuransi karena informasi non-material atau administratif tidak sah menurut hukum. Majelis Hakim menekankan prinsip keadilan kontraktual dan perlindungan terhadap tertanggung. Oleh karena itu, mereka menyatakan bahwa hanya informasi yang bersifat material yang dapat digunakan sebagai dasar yang sah untuk menolak klaim. Aplikasi Penelitian Ini: Hasil penelitian ini dapat digunakan untuk memperkuat perlindungan hukum bagi pemegang polis dalam praktik asuransi jiwa. Selain itu, studi ini dapat digunakan sebagai referensi untuk merumuskan kebijakan dan mereformasi industri asuransi, baik di tingkat nasional maupun regional. Kebaruan/Keaslian Studi Ini: Kebaruan penelitian ini terletak pada pendekatan komparatifnya terhadap prinsip materialitas dalam kontrak asuransi jiwa. Penelitian ini menunjukkan perbedaan antara pendekatan normatif di Indonesia dan pendekatan berbasis bukti faktual di Malaysia, yang memperkaya wawasan tentang perlindungan hukum dalam industri asuransi jiwa serta urgensi pembaruan norma-norma praktis agar lebih adil dan transparan. Kata Kunci: Asuransi Jiwa, Klaim, Keadilan Substansial, Tanggung Jawab Penanggung